KAJIAN EPIZOOTIK Metarhizhium anisopliae PADA LARVA TRITIP (Plutella xylostella L.) (Lepidoptera: Plutellidae) DI RUMAH KACA - Lamsihar O Simamora; Darma Bakti; Syahrial Oemry; Fatiani Manik (Jurnal Agroekoteknologi, 2013)
Epizootic study of Metarhizium anisopliae against Larvae Tritip in greenhouse.                            The objective of this experiment to know the effectiveness of the mechanism of transmission of the fungi M. anisopliae  by larvae tritip in greenhouse. The research was conducted in Greenhouse Crops Research Institute for Tropical Fruit Tongkoh-Berastagi. The research used non-factorial completely randomized design with 5 treatments and 4 replications, which were: control(without infected by M. anisopliae), 5 larvae are infected by (5g, 10g,15g, 20g)/100ml M. anisopliae are transmitted to 5 healthy  larvae. The results showed that the concentration addition  of each suspension fungi M. anisopliae  increased the mortality of larvae infected directly by immersion, mortality is transmitted. The concentration addition of the suspension  fungi M. anisopliae increased transmission between larvae infected directly  immersion method to healthy larvae and can also reduce the intensity of the attacks tritip larvae. The highest percentage of larvae mortality infected directly immersion method was 52,5%. The highest percentage of transmitted larvae  mortality was 32,5% . The highest percentage of entirely larvae mortality was 95% . The highest percentage of larvae  was growed by fungi was 92,5%. The  highest percentage of damage was 59.25%.   Key words : Epizootic, biological control, Plutella xylostella L, Metarhizium anisopliae.